European Community Economics / Third Edition - Hitiris Theo (Harvester Wheatsheaf, 1994)
Recent developments in the ratification of the Maastrict Traety and the Prospects for European Union. Tables, Figures, Abbreviations, Regional Economic Associations: Objectives and Policies and Effects, Structure of the European Community: Objectives and Policies and Constraints, The Single Market, The Community Budget, Tax Harmonization, Monetary Integration, Agriculture, Trade Policies, Regional Policy, Social Policy, Transport, Industrial Policy, Energy and the Environment, Europe 2000: Progress and Prospects, References, Index.